2018
DOI: 10.1101/246777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into circovirus host range from the genomic fossil record

Abstract: A diverse range of DNA sequences derived from circoviruses (family Circoviridae) have been identified in samples obtained from humans and domestic animals, often in association with pathological conditions. In the majority of cases, however, little is known about the natural biology of the viruses from which these sequences are derived.Endogenous circoviral elements (CVe) are DNA sequences derived from circoviruses that occur in animal genomes and provide a useful source of information about circovirus-host re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…We also note that there is a group of cycloviruses recovered from spiders and an insectivorous bat that seem intermediate between other cycloviruses and the circovirus clade ( Manuscript to be reviewed other invertebrates may help resolve phylogenetic relationships among members of the Circoviridae. Nevertheless, our phylogenetic analysis supports the idea that there are distinct groups of cycloviruses (Dennis et al 2018b).…”
Section: Cress Dna Viruses Identified In All Three Major Lineages Of supporting
confidence: 82%
See 2 more Smart Citations
“…We also note that there is a group of cycloviruses recovered from spiders and an insectivorous bat that seem intermediate between other cycloviruses and the circovirus clade ( Manuscript to be reviewed other invertebrates may help resolve phylogenetic relationships among members of the Circoviridae. Nevertheless, our phylogenetic analysis supports the idea that there are distinct groups of cycloviruses (Dennis et al 2018b).…”
Section: Cress Dna Viruses Identified In All Three Major Lineages Of supporting
confidence: 82%
“…All sequences outside of the established CRESS DNA families were grouped by organism (e.g., rodent associated sequences) and sequences within each group were clustered using a 70% amino acid identity cut off. In addition to sequences representing exogenous viruses and replicons, CRESS DNA-like endogenous viral sequences (CEVs) reported from various organisms were included (Dennis et al 2018a;Dennis et al 2018b;Liu et al 2011). Selected CEVs did not contain any early stop codons or frameshifts.…”
Section: Detection Of Cress Dna Viral Genomes and Genome Completionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although spiders harbor a diversity of viruses, there is scarce information regarding the prevalence and ecological impact of viral infection in spiders. Endogenous viral sequences within spider chromosomes indicate that these arachnids have been infected by both CRESS DNA viruses and double-stranded DNA polyomaviruses [19,20]. Studies within the past four years have also revealed a diversity of novel extant viruses in multiple spider species, including more than 20 CRESS DNA [2] and 100 RNA viruses [21][22][23][24] encompassing various viral families and unclassified species.…”
Section: Introductionmentioning
confidence: 99%
“…Circovirus is the smallest nonenveloped icosahedral virus, with a circular, single-stranded genomic DNA, which infects a variety of species ranging from animals to plants with different pathogenicities (20). PCV2, with an unique structural capsid protein, is a representative circovirus that causes significant morbidity and mortality in swine (2123).…”
Section: Introductionmentioning
confidence: 99%